The amazing adventures of John Smith, Jr., aka Houdini - Johnson, Peter, 1951- (Harper, 2012)
Thirteen-year-old John "Houdini" Smith tries to write a book about what is happening in his life, from his parents' worries about money and his brother in Iraq, to his new understandings of people while he and his friends rake lawns in their East Side Providence, Rhode Island neighborhood.